Methodology of production accounting and modeling of management reporting for wine-producing enterprises - Marchuk, Uliana (Herald of Economics, 2025)
Introduction. Wine-producing enterprises operate in an environment with high requirements for quality, authenticity, and transparency of production processes, which necessitates the improvement of production accounting methodology and management reporting modeling. The growing importance of wine tourism as an additional source of income and a component of marketing strategy increases the need to adapt accounting procedures to the specifics of the industry.Brief Literature Review. The scientific literature examines approaches to the organization and methodology of production accounting in the wine industry, the modeling of management reporting, and the integration of accounting information with analytical tools. However, the issue of comprehensive accounting for elements of wine tourism and their reflection in the accounting system of wine-producing enterprises has not been sufficiently researched.Purpose. The purpose of the article is to analyze and systematize methodological approaches to the organization of production accounting in wine-producing enterprises, taking into account the development of enotourism services, as well as to develop management reporting models to improve cost control and support management decisions. Methodology (Data and Methodology). It is based on a combination of analysis and synthesis of scientific sources, comparison and generalization of practical experience of wine-producing enterprises in Ukraine and worldwide, as well as methods of modeling management reporting.Main results of the study are the determination of forms of wine accounting, identification of the components of enotourism and their accounting features, development of the structure of management reporting for wine-producing enterprises, and the format of the report by cost centers. The proposed approaches make it possible to ensure the transparency of information flows, increase the accuracy of accounting data, and integrate them into strategic and operational management processes.Conclusions and prospects for further exploration. The possibility of a comprehensive methodology for production accounting to ensure the competitiveness of wine-producing enterprises and the development of enotourism services is considered.Prospects for further research are related to the integration of digital technologies, in particular blockchain solutions, into the accounting and management reporting system, as well as the development of industry standards for accounting for wine tourism activities.